HARMONIZATION OF LAW AND ECONOMIC POLICY IN REALIZING VISION OF GOLDEN INDONESIA 2045 - Hadi Mulyo Wibowo (RADJA PUBLIKA, 2025)
The Vision of Golden Indonesia 2045 is a strategic projection towards a developed country that is sovereign, just, and prosperous, which requires integration between a strong legal system and economic policies that are oriented towards sustainable and inclusive development. This study aims to analyze how harmonization between law and economic policy can support the achievement of this vision, as well as identify the main challenges in creating synergy between the national legal system and the direction of consistent and adaptive economic policies. The method used is a qualitative-descriptive approach with a literature review of regulations, economic policies, and national planning documents such as the 2025–2045 RPJPN, as well as a study of the practice of implementing economic law in the context of globalization and the digital era. The results of the analysis show that the harmonization of economic law and policy has not been optimal due to overlapping regulations, weak law enforcement, and minimal coordination between policy-making institutions. On the other hand, factors such as legal certainty, investment protection, fair fiscal policy, and support for MSMEs greatly determine the success of long-term economic development. In conclusion, harmonization of law and economic policy is a fundamental prerequisite in realizing the Vision of Golden Indonesia 2045. Systematic regulatory reform, increased capacity of legal institutions, and integration of economic policies that are in line with the principles of social justice, environmental sustainability, and global competitiveness are needed. These synergistic efforts must be carried out consistently by involving public participation, business actors, and law enforcement agencies so that national development can run inclusively and sustainably.